Epicladium Small or Guarianthe Dressler & W.E. Higgins (Orchidaceae)? - Beckner, John (Lankesteriana: International Journal on Orchidology, 2015)
Guarianthe Dressler & W.E.Higgins as a genus has found little favor with orchid growers. If these species are a distinct genus from Cattleya Lindl., under any name, the effects will be substantial. All taxa of this alliance are of considerable horticultural importance, as species and in the ancestry of thousands of garden hybrids. In any case, Guarianthe cannot be replaced by Epicladium Small, which was based on Epidendrum boothianum.